2022
DOI: 10.1002/dvdy.467
|View full text |Cite
|
Sign up to set email alerts
|

Rbbp4 loss disrupts neural progenitor cell cycle regulation independent of Rb and leads to Tp53 acetylation and apoptosis

Abstract: Background: Retinoblastoma binding protein 4 (Rbbp4) is a component of transcription regulatory complexes that control cell cycle gene expression. Previous work indicated that Rbbp4 cooperates with the Rb tumor suppressor to block cell cycle entry. Here, we use genetic analysis to examine the interactions of Rbbp4, Rb, and Tp53 in zebrafish neural progenitor cell cycle regulation and survival. Results: Rbbp4 is upregulated across the spectrum of human embryonal and glial brain cancers. Transgenic rescue of rbb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Another transcription factor with parallel mutations that affected gene expression was HMPREF1120_05223. The top 2 co-expressed genes include chromatin packing genes H2A/H2B and H3/H4 histone acetyltransferase (HMPREF1120_07775) and RBBP4 (HMPREF1120_07289), which are also involved in DNA repair ( 43 , 44 ). Two genes that correlated with the transcription factor are involved in protein synthesis: glutamyl-tRNA synthetase (HMPREF1120_03118) and elongator complex protein 1 (HMPREF1120_03655).…”
Section: Resultsmentioning
confidence: 99%
“…Another transcription factor with parallel mutations that affected gene expression was HMPREF1120_05223. The top 2 co-expressed genes include chromatin packing genes H2A/H2B and H3/H4 histone acetyltransferase (HMPREF1120_07775) and RBBP4 (HMPREF1120_07289), which are also involved in DNA repair ( 43 , 44 ). Two genes that correlated with the transcription factor are involved in protein synthesis: glutamyl-tRNA synthetase (HMPREF1120_03118) and elongator complex protein 1 (HMPREF1120_03655).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that, according to the literature data, they seemingly act in regulating the balance between pro-apoptotic and cell survival signals. Data on these elements mainly refer to their role in carcinogenesis [57][58][59]. Nevertheless, some hypotheses can be drafted from this data: the down-regulation of HMGN4 and RBBP4, as well as the up-regulation of KDM5D tend toward pro-apoptotic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, reducing its expression may trigger an opposite effect, promoting cell cycle arrest and apoptotic signaling. Finally, it has been observed that RBBP4 loss disrupts neural progenitor cell cycle regulation and leads to Tp53 acetylation and apoptosis [59].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in yeast and cultured cells have shown that RBBP4 appears to function as a tumor suppressor along with RB, leading to inhibition of cell cycle progression and cell growth ( 16 , 18 ). Nevertheless, Schultz-Rogers et al ( 31 ) indicated that RBBP4 is essential for the cell cycle progression of neural progenitor cells and the initiation of G 0 , irrespective of the involvement of RB. The E2F family plays a key role in cell cycle regulation, and all RB family members interact with typical E2F proteins to form transcriptional inhibition complexes ( 32 ).…”
Section: The Biological Functions Of Rbbp4/7mentioning
confidence: 99%